دور المقاول في ترشيد السلوك البيئي للمؤسسة "دراسة استطلاعية على عينة من المقاولين بولاية الأغواط" (Revue El-Wahat pour les Recherches et les Etudes, 2015)
This paper seeks to identify the role of entrepreneur in rationalization the environmental behavior through an exploratory study on a sample of entrepreneurs in Laghouat city, the study identified by a researched variable represent in (the environmental behavior) and by an independent variable represent in (the entrepreneur behavior) who identified three internal variables represented in (legal behavior , ethical behavior and voluntary behavior) and as an external variable represent restructuring Entreprise included (entrepreneurial activity, creation day and size).          To achieve the study objectives, questionnaire was developed for the purpose of collecting data from respondents, and reached a population of 35 single, we used Statistical Package for Social Sciences (SPSS) for analysing questionnaire data, depending on the mean, regression and variance analysis and other statistical methods analysis, it has reached some results, most notably:- That all external variables (entrepreneurial activity, creation date, size) contribute to determine the environmental behavior.- The internal variable (legal behavior) Contribute directly in the rationalization of environmental behavior.- There is no role for the voluntary and moral behavior of the entrepreneur in the rationalization of environmental behavior.          The study recommends the end the need to respond the entrepreneur with the requirements of sustainable development by changing his behaviors and actions to the environmental resources to be more moderation and less consumption of natural resources, especially since the study had concluded that there is only a role for legal behavior, without the voluntary and ethical behavior of the entrepreneur in the rationalization of environmental behavior. Key words: environmental behavior, legal behavior, moral behavior, voluntary behavior, entrepreneur.